TMEM70 facilitates biogenesis of mammalian ATP synthase by promoting subunit c incorporation into the rotor structure of the enzyme - Kovalčíková, Jana; Vrbacký, Marek; Pecina, Petr; Tauchmannová, Kateřina; Nůsková, Hana; Kaplanová, Vilma; Brázdová, Andrea; Alán, Lukáš; Eliáš, Jan; Čunátová, Kristýna; Kořínek, Vladimír; Sedlacek, Radislav; et al. (The FASEB journal, 2019)
Biogenesis of F1Fo ATP synthase, the key enzyme of mitochondrial energy provision, depends on transmembrane protein 70 (TMEM70), localized in the inner mitochondrial membrane of higher eukaryotes. TMEM70 absence causes severe ATP-synthase deficiency and leads to a neonatal mitochondrial encephalocardiomyopathy in humans. However, the exact biochemical function of TMEM70 remains unknown. Using TMEM70 conditional knockout in mice, we show that absence of TMEM70 impairs the early stage of enzyme biogenesis by preventing incorporation of hydrophobic subunit c into rotor structure of the enzyme. This results in the formation of an incomplete, pathologic enzyme complex consisting of F1 domain and peripheral stalk but lacking Fo proton channel composed of subunits c and a. We demonstrated direct interaction between TMEM70 and subunit c and showed that overexpression of subunit c in TMEM70-/- cells partially rescued TMEM70 defect. Accordingly, TMEM70 knockdown prevented subunit c accumulation otherwise observed in F1-deficient cells. Altogether, we identified TMEM70 as specific ancillary factor for subunit c. The biologic role of TMEM70 is to increase the low efficacy of spontaneous assembly of subunit c oligomer, the key and rate-limiting step of ATP-synthase biogenesis, and thus to reach an adequately high physiologic level of ATP synthase in mammalian tissues.-Kovalčíková, J., Vrbacký, M., Pecina, P., Tauchmannová, K., Nůsková, H., Kaplanová, V., Brázdová, A., Alán, L., Eliáš, J., Čunátová, K., Kořínek, V., Sedlacek, R., Mráček, T., Houštěk, J. TMEM70 facilitates biogenesis of mammalian ATP synthase by promoting subunit c incorporation into the rotor structure of the enzyme.
Keywords: Proteolipids; Cells, Cultured; lidé; mitochondriální protonové ATPasy; Mice, Knockout; Gene Expression Regulation; genový knockout; kultivované buňky; myši; Humans; Genotype; Mice; HEK293 buňky; mitochondriální proteiny; Tamoxifen; zvířata; Mitochondrial Proton-Translocating ATPases; Animals; myši knockoutované; genotyp; proteolipidy; Gene Knockout Techniques; tamoxifen; regulace genové exprese; HEK293 Cells; Mitochondrial Proteins